Design and Develop a Web-Based Social Assistance Recipient Information System At The Ministry Of Social Affairs Of The Republic Of Indonesia - Nirmalawati , Zara; Sudarsono, Bernadus Gunawan; Sharyanto, Sharyanto (Yayasan Bina Internusa Mabarindo, 2024)
The Ministry of Social Affairs of the Republic of Indonesia is responsible for implementing and overseeing domestic affairs within the government to assist the President in governing the country in the social sector and is accountable for the distribution of social assistance in Indonesia. The process of data collection, identification, monitoring, as well as limitations in accessibility and information is so challenging that it causes many citizens to be unaware of information regarding social assistance. The data collection methods used in this research are Observation Method, Interview Method, and Literature Study Method. This research also includes system modeling using the UML (Unified Modeling Language) method as well as PHP (Hypertext Preprocessor) as the programming language and MySQL as the Database used for the development of the